Prevalence, practice, and determinants of self-medication among the common public in a village of Northern Kerala, India - G., Narayanan Namboothiri; K. C., Lamees; Latheef, Tamanna; M. M., Thasleema; Muhammed N., Thameem; R., Swathi (International Journal of Research in Medical Sciences, 2023)
Background: Self-medication, managing health issues without professional guidance, poses significant risks to individuals and public health. Prevalence rates vary globally, often higher in low-income countries due to limited healthcare access. While self-medication offers cost-effective solutions for minor ailments, it may lead to misuse, adverse effects and financial burdens. Identifying factors driving self-medication is crucial for tailored interventions. This study aims to assess self-medication prevalence, practice, and influencing factors in a Kerala village. Methods: A community-based cross-sectional study included 212 participants (≥18 years) selected via convenient sampling. A pre-tested questionnaire collected socio-demographic data, self-medication prevalence, and influencing factors. Self-medication was defined as OTC drug use without consulting a medical graduate. Data were analyzed using SPSS 26, with chi-square tests for bivariate analysis (p≤0.05). Results: Participants (mean age: 38.13±15.56) reported 53.8% self-medication. Acute illness individuals self-medicated more (80.7% purchased from independent pharmacies). Time constraints (24.5%) and expired prescriptions (42.1%) drove self-medication. Medication choice was influenced by cost (54.3%), brand reputation (21.1%), and both (24.6%), with pharmacist recommendations (36.0%) playing a role. Self-medication was common among ages 41-60 (64.3%) and those with lower education levels (77.8% primary, 70.5% middle). Acute illness individuals self-medicated more (66%) than chronic cases (34%). Conclusions: This rural Kerala study identifies a 53.8% self-medication rate, affected by age, education, and healthcare preferences. Targeted interventions are needed for ethical self-medication and improved healthcare practices.